Fundamental Requirement for Instituting Reforms on Ukraine’s Route to European Integration - Chorna, Alona Ihorivna (Державний податковий університет, 2023)
A list of requirements for reforms in Ukraine on the path to European integration, in particular in the field of humanities, is presented. At its core, these are paradigms of innovative economic development, supported by a complex process of constant renewal, which includes not only the diversification and improvement of goods and services, but also the constant improvement of technologies inherent in their production. This is a complex interaction of innovation and economic evolution, which not only fuels economic growth, but also increases the overall competitiveness of the nation on the global stage.

Представлено перелік вимог до проведення реформ в Україні на шляху до європейської інтеграції, зокрема у галузі гуманітарних наук. У своїй основі це парадигми інноваційного економічного розвитку, що підкріплюються складним процесом постійного оновлення, що включає не лише диверсифікацію та покращення товарів і послуг, а й постійне вдосконалення технологій, невід’ємних від їх виробництва. Це складна взаємодія інновацій та економічної еволюції, що не лише підживлює економічне зростання, але також підвищує загальну конкурентоспроможність нації на глобальній арені.
Keywords: development; innovation; reforms; revival; розвиток; інновації; реформи; відродження